(untitled) (Lingue e culture dei media, 2022)
Fin dalla sua uscita nel 1954, Senso, il film di Luchino Visconti tratto dall’eponimo racconto di Camillo Boito (1883), ha suscitato l’attenzione degli studiosi. Mancava però uno studio dedicato agli aspetti linguistici. In questo contributo si indaga la lingua del film, cercando, se possibile, di sottolineare il rapporto tra codice verbale e codice visuale. Attenzione è stata anche dedicata al rapporto tra l’italiano filmico e quello del testo boitiano. Since its realise in 1954, Senso, the film by Luchino Visconti based on the eponymous short story by Camillo Boito (1883), has attracted the attention of scholars. However, a study dedicated to linguistic aspects was missing. This contribution investigates the language of the film, tryng, if possible, to underline the relationship between verbal code and visual code. Attention was also paid to the relationship between filmic italian and that of Boito’s text. Senso, one of the most important film by Luchino Visconti, is based on the Camillo Boito’s short story written in 1883. Since it was realised in 1954, many were the scholars interested in studying Senso, but a language study was still missing. This paper introduces a linguistic analysis of the film and tries to emphasizes two types of relationship: the connection between verbal code and visual code and the dialogue between Visconti and Boito’s text.